Balancing Work and Life Promotes Job Satisfaction – Generational Gap among Medical Doctors - Perumal, Kala Premarani (2013)
The profession of a doctor is considered to be one of the noblest professions. Doctors in general work around the clock in their deed of saving human lives and relieving them of physical ailments. However, on their personal front, most of them do not find them to fulfil their personal obligations. A work-life balance, which is nothing but the art of balancing personal and professional lives, is important for any individual to have fulfilment and satisfaction in life. This research intended to investigate in detail how doctors or medical practitioners belonging to different generations who are demanded to work around the clock perceive the work-life balance and how it is associated with their levels of job satisfaction. In order to attain the research objectives, the researcher has adapted a quantitative approach. A total of 158 doctors from Klang Valley, Malaysia have been surveyed for the study using questionnaires containing closed-ended questions. Fundamental objectives of this research were to identify how a work-life balance promotes job satisfaction between generations and solutions that overcome behaviours that limit doctors in integrating both work and life. The analysis proved that a work-life balance is a definite tool to achieve job satisfaction, and doctors born prior to the 1980s, who have been practising medicine for a long time, maintain a better work-life balance when compared with that of the younger-generation doctors driven by their higher job satisfaction level. One of the main stumbling blocks faced by the doctors is the organisational culture that lacks in promoting this balance despite the range of work-life balance programmes made available. Finally, this research provides some recommendations that would help doctors of all generations maintain a perfect balance between their work and personal lives.